Seroprevalence of Salmonella and Mycoplasma gallisepticum Infection in the Six Model Breeder Poultry Farms at Patuakhali District in Bangladesh - Sikder, A.J.; Islam, M.A.; Rahman, M.M.; Rahman, M.B. (International Journal of Poultry Science, 2005)
The present study was undertaken to know the seroprevalence of Salmonella and Mycoplasma gallisepticum (MG) infection in six model breeder poultry farms (MBPFs) located at kalapara Upazilla under Patuakhali district, Bangladesh. A total of 364 sera samples were collected from chickens belonging to six MBPFs. All sera samples were examined by rapid serum plate agglutination (SPA) test using commercial Salmonella (SP) and MG antigens to determine the presence of Salmonella and MG specific antibodies in different age and sex of birds belonging to MBPFs. In addition to that prevalence of Salmonella and Mycoplasma infection in MBPFs during rainy and winter seasons were also recorded. The results of serological tests were analyzed statistically. The overall prevalence of Salmonella and Mycoplasma infection in six MBPFs were recorded as 23.46% and 46.88% respectively. Prevalence of salmonella was recorded highest in rainy season (25.00%) than the winter season (21.88). On the contrary, Mycoplasma infection was recorded highest in winter season (61.45%) than the rainy season (51.74%). Both Salmonella and Mycoplasma infections were recorded highest in female birds (24.10%) than the male birds (15.62%). The prevalence of MG infection decreased with the increase of age. MG infection recorded highest 71.42% at 18 weeks of age and lowest 50% at 22 weeks of age. On the other hand, the prevalence Salmonella infection was increased with the increase age. Salmonella infection was found highest 30.76% at 39 weeks of age and lowest 13.33% at 32 weeks of age. It was concluded from the present study that both Salmonella and MG infection were significantly present in all six MBPFs and SPA test could be used as a tool for quick detection of Salmonella and MG infection.